Gold investment and fintech / Jalaluddin Mahamod … [et al.] - Mahamod, Jalaluddin; Aziz, Muhammad Amirul Firdaus; Dzalihu'zzabir, Muhammad Fakhrul Hadi; Ruslan, Muhammad Fauzan (2023)
Investing in gold has been one of the most consistent choices in the ever-changing world of finance. As an asset that has been trusted for centuries, gold has continued appeal as a stable hedge amid market uncertainty. Its long history as a medium of exchange and store of value has shaped the image of gold as a universally recognized wealth. Its existence has survived various economic periods, crossed various financial crises, and remained one of the preferred investment instruments to face market volatility. The high intrinsic value of gold, offset by its limited availability, has provided a strong basis for its stable value. This makes it a top choice for investors looking for protection against inflation, currency devaluation, or economic turbulence. As an important part of a portfolio diversification strategy, gold offers resistance to market fluctuations that are not related to the performance of the stock or bond market.